Diagnóstico da Leishmaniose Visceral canina em uma área de transmissão recente: mais de 25% dos cães soronegativos estavam infectados - Gondim, Carolina Novato (2019)
American Visceral Leishmaniasis (AVL) is a parasitic disease that has the dog as the main domestic reservoir and is caused by the protozoan Leishmania infantum, being considered one of the most important zoonosis in the context of public health. In the last decades, the increasing expansion and urbanization of LVA in Brazil has been observed and the municipality of Lavras / MG is a new area of epidemiological investigation. The Ministry of Health recommends the use of the quick test (TR) DPP® for diagnostic screening of Canine Visceral Leishmaniasis (LVC), and the positive cases are confirmed by Bio-Manguinhos enzyme immunoassay (EIE). However, research shows a low sensitivity of TR DPP® in dogs without clinical signs. In view of the above, this cross - sectional study aimed to analyze the performance of different methodologies used in the diagnosis of LVC, using parasitological and molecular tests as a reference standard; in dogs sampled from the municipality of Lavras and surrounding cities, segregated by the clinical condition. The sample consisted of 52 dogs separated into groups with absence and presence of clinical signs of LVC. The following techniques were performed: TR DPP® with whole blood collected by the tip of the ear and with venous blood; TR ALERE®, TR and EIE with the rKDDR-plus protein; direct parasitological aspiration of bone marrow; PCR of the sample collected with conjunctival swab and bone marrow. The sensitivity values obtained in dogs with clinical signs present and absent were respectively: TR DPP® ear tip (93 and 47%); TR DPP® venous blood (93 and 52%); TR ALERE® (79 and 42%); TR rKDDR-plus (86 and 52%); EIE rKDDR-plus (86 and 57%); direct parasitological bone marrow (20 and 9%); Conjunctival swab PCR (94 and 87%); Bone marrow PCR (100 and 90%). The specificity values could not be evaluated because the true negatives in the sample were lower. It was concluded that more than 25% of the negative serum dogs are infected and the serological tests presented unsatisfactory results of sensitivity in dogs without clinical signs to be classified as screening tests. It is suggested that PCR with conjunctival swab should be used as a screening test in dogs without clinical signs because it is a non-invasive collection technique and presents high sensitivity values.